Managing innovation as communicative processes: A case of subsea technology R&D - Tone Merethe Berg Aasen; Stig O. Johannessen (International Journal of Business Science & Applied Management (IJBSAM), 2009)
Exploration of the communicative nature of innovation processes and the impact of this on innovation management has largely been ignored in innovation research. This paper suggests that the adoption of a complex responsive processes perspective opens up for insight and implications that depart from the prevailing view of what it means to manage joint efforts for innovation in business organizations. A key contribution is the suggestion that a change of perspective on organizations from conceptions of 'whole' to notions of joint human interaction implies a need to increase management attention to the detail of local interaction between people striving to construct meaning out of new and ongoing themes, for the company and for them. We base our claims on an empirical example, drawn on a longitudinal research initiative conducted in cooperation with the Norwegian petroleum company Statoil.
Keywords: 650; complex responsive processes; innovation management; innovation processes; subsea increased oil recovery